Performance-Based Seismic Design of High-Rise Buildings: Incorporating Nonlinear Soil-Structure Interaction Effects - Ande, Janaki Rama Phanendra Kumar (Engineering International, 2018)
This project aims to understand better how to incorporate nonlinear soil-structure interaction (SSI) effects into high-rise building performance-based seismic design approaches. The primary goals are to determine how important it is to include nonlinear SSI effects, create integration methods for them, and analyze how they affect seismic resilience. In terms of methodology, the study uses case studies and an analysis of current literature to show real-world applicability. Important discoveries highlight how critical nonlinear SSI analysis is for precisely forecasting structural reactions, locating weaknesses, and creating focused mitigation strategies. The policy implications emphasize the necessity of modern building regulations, research and development expenditures, and advancements in site characterization methods to facilitate the implementation of performance-based design methodologies. To improve the resilience and safety of high-rise buildings in earthquake-prone areas, this study's findings highlight the significance of considering nonlinear SSI effects during seismic design procedures.
Keywords: Seismic Performance; High-Rise Buildings; Nonlinear Soil-Structure Interaction; Seismic Hazards; Structural Engineering; Performance-Based Design; Earthquake Resistance